JUDGEMENT STATE AUDITOR ON AUDIT OPINION FOR GOVERNMENT FINANCIAL STATEMENT WITH PERSPECTIVE HERMENEUTIC PHENOMENOLOGY - Susanto, Dwi Setiawan; Sudarma, Made; -, sutrisno; -, rosidi (The International Journal of Accounting and Business Society, 2019)
Background. The Audit Act no 15, 2004 stated that audit opinion is based on 4 (four) criterias, which are accounting standard, compliance on law and regulation, effectivity internal control system and full disclosure. Public accountability quality of financial statement that audited by BPK RI should be based on State Finance Audit Standard (SPKN) and audit system or guidelines to attest the truth and fairness of the judgement. State finance auditor will make audit judgement for audit opinion based on all material of financial statement, not only in quantitative but also qualitative manner of significance financial information as part of public accountability. However, audit process is not only depends on structured standard system approach but also influenced by individual (auditor) subjectivity. Auditor subjectivity is difficult to be avoided during the audit process and may play a role in the audit judgement and final audit opinion.Objective. Our study aims to analyze the role of BPK RI auditor subjectivity during audit judgement in government institution and in making final audit opinion, using interpretive hermeneutic phenomenology.Methods. Our study analyzed audit judgement with interpretive process hermeneutic and phenomenology perspective.Results. We conducted in-depth interviews with BPK audit opinion signing auditors and analyzed how auditor interpreted audit data, in regards with the basic principles of public accountability, audit standard, law and regulation, internal control and complexity organization in the auditee institution. Our study found differences among auditors in interpreting audit data based on different perspective and understanding of standard system, law and regulation and complexity of organization, mostly because they did not use basic principles of public accountability during the process and making audit judgement and final audit opinion.Conclusion. Our results came to understanding that auditors should be using basic principles of public accountability when interpreting audit data, audit standard, law and regulation to improve quality of audit judgement. Auditors of BPK as supreme audit institution in Indonesia should combine all aspects in auditing process and making final audit judgment.Key words : Audit Opinion, Public Accountability, Audit Judgement, Hermeneutic Phenomenology.